Constitutional Moments, Precommitment, and Fundamental Reform: The Case of Argentina - Geoffrey P. Miller (Washington University Law Quarterly, 1993)
In this Article, I will consider how Argentina has addressed two universal problems: effecting fundamental reform in the presence of powerful vested interests and precommitting to restrain undesirable behavior by the government in the face of political pressures for short-term solutions.
Keywords: Economics; Practical politics -- Argentina